Audit Keamanan Sistem Akuntansi Enterprise PT. Gresik Cipta Sejahtera Berdasarkan Standar ISO 27002:2005 - Sastra, I Putu Narario; Tanuwijaya, Haryanto; Sutomo, Erwin (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT. Gresik Cipta Sejahtera (PT. GCS) is a company with a core business field of trade of fertilizers and chemicals in the environment PKG Group subsidiary. PT. GCS has implemented information technology such as enterprise accounting system (SAE), which has been operating for the last 1 year. As for problems that occur during the operation of SAE, namely: 1. Confidentiality error posting sales transactions that are not according to plan, 2. Integrity integrity of property, especially in IT and financial statements did not balance, and 3. Availability of information provision delay budgeting.To determine the level of security SAE ongoing, so do security audits SAE PT. GCS Based on ISO Standard 27002: 2005. The scope of the audit used are: 1. Clause 7 (Asset Management), 2. Clause 8 (Security Human Resources), 3. Clause 9 (Physical Security and Environment), and 4. Clause 11 (Access Control).The value of the maturity level of security aspects confidentiality obtained was 2:53 while the security aspects of integrity and availability are included in the category of managed 2.78, which means most of the process is planned and implemented with limited documentation. The resulting recommendations are making policy and complements the information security procedures to reduce information security risks and improve information security SAE PT. GCS.Keywords: Audit, Information Security, ISO 27002:2005, level of maturity.